Implantable cardioverter defibrillators in the context of hypertrophic cardiomyopathy: a lesson in patient autonomy. (5th February 2018) - Bray, Jonathan James Hyett; Bucciarelli-Ducci, Chiara; Stuart, Graham
Abstract : Hypertrophiccardiomyopathy (HCM) is common, whereas the decision not to have an implantable cardioverterdefibrillator (ICD) when probably falling into a 'high-risk' category is not. A solicitor aged 45 years attended the inherited cardiac conditions clinic for review of her HCM and discussion about ICD implantation for primary prevention of sudden cardiac death (SCD). Despite a predicted 7% risk of SCD within the next 5 years, according to the European Society of Cardiology endorsed HCM Risk-SCD risk stratification tool, the patient opted against implantation of an ICD and comprehensively justifies her decision. This report discusses ethical aspects of a consultation offering ICD protection against SCD in the context of HCM and emphasises the clinicians' role in respecting patient autonomy.